2009
DOI: 10.1007/s10750-009-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling streambed coverage of Didymosphenia geminata in two regulated streams in the Colorado Front Range

Abstract: Didymosphenia geminata is a stalk-forming freshwater diatom which was historically found primarily in oligotrophic lakes and streams, but has recently become a nuisance species in many lotic systems worldwide. In the last 5-8 years, D. geminata has become established in Boulder Creek and South Boulder Creek, two regulated montane streams in the Front Range of the Colorado Rocky Mountains. Factors that may influence the growth of D. geminata were monitored during the summer of 2006. D. geminata abundance decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 15 publications
4
37
0
Order By: Relevance
“…For example, Miller et al (2009) reported a negative correlation between D. geminata abundance and total dissolved P. Slow-release granular fertilizer addition was applied to Rapid Creek (South Dakota) to increase nutrient supply (Larson and Carreiro, 2008). For example, Miller et al (2009) reported a negative correlation between D. geminata abundance and total dissolved P. Slow-release granular fertilizer addition was applied to Rapid Creek (South Dakota) to increase nutrient supply (Larson and Carreiro, 2008).…”
Section: Managementmentioning
confidence: 99%
“…For example, Miller et al (2009) reported a negative correlation between D. geminata abundance and total dissolved P. Slow-release granular fertilizer addition was applied to Rapid Creek (South Dakota) to increase nutrient supply (Larson and Carreiro, 2008). For example, Miller et al (2009) reported a negative correlation between D. geminata abundance and total dissolved P. Slow-release granular fertilizer addition was applied to Rapid Creek (South Dakota) to increase nutrient supply (Larson and Carreiro, 2008).…”
Section: Managementmentioning
confidence: 99%
“…Didymo prefers oligotrophic riverine sites with low mean discharge and stable flows, as flashy, high flows tend to scour algal mats from the river bottom (Miller et al 2009). Schwieger et al (2011) found that higher stream temperatures and reduced distance from upstream lakes (as a proxy for stable base flows) were among the top predictors of elevated didymo abundances that can be related to recent climate change.…”
Section: Didymo: a Sentinel Of Climate-induced Change In Gaspésie Rivmentioning
confidence: 99%
“…Didymo is a colonial diatom found in North America and Europe (Patrick and Reimer 1975;Blanco and Ector 2009). It can form extensive, thick mats on rocks and benthic substrates in unshaded stretches of rivers or streams (Kirkwood et al 2007) with stable base flows (Miller et al 2009) and low nutrient concentrations (Spaulding and Elwell 2007). These persistent mats can alter the benthic substrate, providing additional habitat for periphyton (Kilroy et al 2009), which increases the density of smallbodied benthic invertebrates and alters invertebrate community composition (Gillis and Chalifour 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Didymo generally prefers low-nutrient riverine sites with low mean discharge and stable stream flows, since flashy, high flows tend to scour blooms from the river bottom 27 and alter water chemistry and light regimes. Recent warming is known to reduce the extent and duration of lake and river ice 28 , including its seasonality, and also cause shifts in both the timing and intensity of disturbance regimes (flow, ice scour, river bed movement) of rivers and streams 29 .…”
Section: Didymo: a Sentinel Of Climate-induced Change In Gaspésie Rivmentioning
confidence: 99%
“…"Rock snot" is the common name for a colonial diatom classified as Didymosphenia geminata 2 (hereafter "didymo"), which is often found in North American and European rivers. It can form extensive mats several centimeters thick (referred to as blooms) on the bottoms of unshaded stretches of rivers or streams with stable flow patterns and often low nutrient concentrations 3,4,5 . Blooms can alter the river bottom, with implications for many organisms 1,6,7 .Many government agencies currently recognize didymo as an introduced species with the ability to affect the structure and function of river ecosystems 8 .…”
Section: Introductionmentioning
confidence: 99%